POTENSI DAN STRATEGI PENGEMBANGAN BANK SYARI’AH DI INDONESIA: KAJIAN PRODUK SYARI’AH DARI SEGI FIQIH MU’AMALAT - Anny Ratnawati (Jurnal Hukum Islam, 2011)
At the present, Indonesia operate dual banking system that are conventional banking system with its interest rate runs side by side and the Islamic banking with the profit-sharing/non-interest system of its own. Islamic banking using fiqih mu’amalat as the basic theory in the syari’ah product. In general, community’s respond toward Islamic bank is good relatively that shown by the trend of Third Parties Funding and Financing to Deposit Ratio with low level of Non Performing Loan. This paper assess the consumer’s preference toward both conventional and Islamic banking, in related with analysis of potency and development strategy of Islamic banking in Indonesia by using fiqih mu’amalat as the basic theory. The analysis of data by using qualitatively (descriptive) analysis, cross tabulation, and logistic regression model. Literature study used in this paper. In general, community’s attitude toward interest rate system still ambiguous, that are interest rate is contrary to syari’ah of Islam, meanwhile in banking transaction they still use conventional system. The reasons that motivate consumer to adopt Islamic banking related to professionalism of bank, security, and pleasure in doing transaction, strategic location, and the implementation of syari’ah system. However, community still has difficulties to comprehend the technical term of Islamic banking. Thus, socialization and education process about economic system of Islam (syari’ah economic) designate necessary requirement in encourage the development of Islamic banking in the future.